Intestinal Carriage of Two Distinct stx2f-Carrying Escherichia coli Strains by a Child with Uncomplicated Diarrhea - Florence Crombé; Angela H. A. M. van Hoek; Heleen Nailis; Frédéric Auvray; Toon Janssen; Denis Piérard (Pathogens)
Two distinct stx2f-carrying Escherichia coli (E. coli) strains, isolated from a child with uncomplicated diarrhea fifteen weeks apart, were characterized by combining short- and long-read sequencing to compare their genetic relatedness. One strain was characterized as Shiga toxin-producing E. coli (STEC)/typical enteropathogenic E. coli (tEPEC) O63:H6 with a repertoire of virulence genes including stx2f, eae (α2-subtype), cdt, and bfpA. The other STEC with serotype O157:H16, reported for the first time as stx2f-carrying Escherichia coli in this study, possessed, in addition, eae (ε-subtype) and cdt, amongst other virulence-related genes. BLAST comparison showed that the stx2f-harboring prophage sequences of both strains were highly homologous (99.6% identity and 96.1% coverage). These results were corroborated by core Stx2f phage Multilocus Sequence Typing (cpMLST) as the stx2f-harboring prophages of both isolates clustered together when compared to those of 167 other human stx2f-carrying Escherichia coli. Overall, the stx2f-harboring prophages of the two distinct E. coli strains isolated from the present case were highly similar, suggesting that the stx2f-harboring phage might have been transferred from the STEC/tEPEC O63:H6 strain to the atypical EPEC (aEPEC) O157:H16 strain in the gut of the child.